Primerjava slovenskega učbeniškega kompleta za učni predmet družba z avstrijskim učbeniškim kompletom za učni predmet geografija in gospodarstvo - Fartelj, Viktorija; Hus, Vlasta (Revija za elementarno izobraževanje, 2009)
Comparison of Slovene textbooks for the subjects. The purpose of this research was to find out the variety and complexity of textbooks for the subjects "society" in the fifth class of the nine-year elementary school system in Slovenia and "geography and economics" in the first class of the fifth educational stage of the general obligatory school in Austria. A comparison between Slovene and Austrian textbooks, according to defined criteria, was also carried out. The research included Slovene textbooks for the subject "society" for the fifth class and Austrian textbooks for the subject "geography and economics" for the fifth stage of the general obligatory school. The research revealed that there is a greater variety in textbooks that are offered in Austria for the subjects mentioned above, but there is a greater complexity in the Slovene textbooks. The comparison of Slovene and Austrian textbooks shows some differences in the aims defined in the textbooks and the aims of the national curriculum and differences among the individual teaching aids that are provided with the textbooks. These textbooks also show some similarities, such as the stimulation of active learning and teaching and the stimulation of connecting different subjects and images that are outside the usual characteristics of these types of textbooks.